The Way of Oz : A Guide to Wisdom, Heart, and Courage - Smith, Robert V., 1942- (Book collections on Project MUSE., 2012)
"A model for personal and professional development based upon the story and characters of The Wizard of Oz and the life of its author, L. Frank Baum. Discusses the intellectual, moral, and ethical value of lifelong learning, loving, and serving others with humility and a focus on the future"--Provided by publisher.